Audit and evaluation: Working collaboratively to support accountability. (April 2020) - Naidoo, Indran
Audit and evaluation play crucial roles in the oversight function of organizations. Both professions share commonalities that have led some to call for "enhanced oversight" through stronger collaboration of the two functions. Our experience suggests that joint assessments can help promote a holistic three-dimensional view of performance, which looks both inside and outside organizations to see whether inputs matched with outputs and outcomes. However, tangible differences in paradigm and approach need discussion before further convergence of the functions is countenanced. The separation of the two functions ensures their independence, which is a guarantee of the credibility of the auditors and evaluators' work.